Long‐Living Holes in Grey Anatase TiO2 Enable Noble‐Metal‐Free and Sacrificial‐Agent‐Free Water Splitting. Issue 18 (14th August 2020) - Liu, Ning; Mohajernia, Shiva; Nguyen, Nhat Truong; Hejazi, Seyedsina; Plass, Fabian; Kahnt, Axel; Yokosawa, Tadahiro; Osvet, Andres; Spiecker, Erdmann; Guldi, Dirk M.; Schmuki, Patrik
Abstract: Titanium dioxide has been the benchmark semiconductor in photocatalysis for more than 40 years. Full water splitting, that is, decomposing water into H2 and O2 in stoichiometric amounts and with an acceptable activity, still remains a challenge, even when TiO2 ‐based photocatalysts are used in combination with noble‐metal co‐catalysts. The bottleneck of anatase‐type TiO2 remains the water oxidation, that is, the hole transfer reaction from pristine anatase to the aqueous environment. In this work, we report that "grey" (defect engineered) anatase can provide a drastically enhanced lifetime of photogenerated holes, which, in turn, enables an efficient oxidation reaction of water to peroxide via a two‐electron pathway. As a result, a Ni@grey anatase TiO2 catalyst can be constructed with an impressive performance in terms of photocatalytic splitting of neutral water into H2 and a stoichiometric amount of H2 O2 without the need of any noble metals or sacrificial agents. The finding of long hole lifetimes in grey anatase opens up a wide spectrum of further photocatalytic applications of this material. Abstract : Long‐living photogenerated holes : Grey anatase, in comparison to white anatase, provides a drastically enhanced lifetime for trapped photogenerated holes. This allows to construct a Ni@grey anatase TiO2 catalyst that can photocatalytically split neutral water into H2 and a stoichiometric amount of H2 O2 without the need of any noble metals or sacrificial agents.Institute and/or researcher Twitter usernames: @FAU_Germany